Report of the Working Group on Participatory Irrigation Management Programme for The IX Five Year Plan - Planning Commission (Planning Commission, 1997)
The Working Group held its first meeting on 3.1.96. There were extensive discussions on various aspects of PIM, resulting in a broad agreement on the general structure which should be adopted for the report of the Group, and its main contents and thrust. The Working Group participated in the Seminar on Irrigation Management Transfer organized by the International Irrigation Management Institute, Colombo and the Indian Institute of Management Ahmedabad at Delhi on 13.3.96, following which the Group held its second meeting where the discussions continued. In accordance with the agreed structure of the report the Group set up different sub-groups to prepare broad outlines of the various chapters.
Government of India Ministry of Water Resources Command Area Development Wing
Government of India Ministry of Water Resources Command Area Development Wing